Daya Terima dan Kandungan Serat Cookies dengan Substitusi Ubi Jalar Ungu dan Penambahan Biji Chia sebagai Alternatif Snack Tinggi Serat untuk Remaja Awal - Resky Aulyas Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Inadequate dietary fiber intake may present a risk of inhibiting the final catch-up process in young adolescents. Therefore, it is vital to find solutions to this issue, one of which is the creation of fiber-rich products. This study was conducted to determine the acceptability (color, scent, texture, and taste) of cookies with different levels of purple sweet potato substitution and the addition of chia seeds, as well as the fiber content of the best cookie formula. This quantitative research with pure experimental methods uses a research design in the form of a completely randomized design (CRD) consisting of six different treatments, namely (80%, 15%); (80%, 10%); (75%, 15%); (75%, 10%); (70%, 15%); and (70%, 10%). A questionnaire will be used as the study tool, and 35 semi-trained panelists will complete it. The Kruskal-Wallis test was used as the statistical test in this study, and an extra test in the Mann-Whitney test was used if the p-value was less than 0.05. The results showed that the substitution of purple sweet potato and the addition of chia seeds had an effect on color and taste, so Ha was accepted for both characteristics. However, the substitution of purple sweet potato and the addition of chia seeds did not affect the scent and texture, so Ha was rejected for aroma and texture. The cookies with the best hedonic test results were F5 (70%; 15%) with a dietary fiber level of 6.61 g per 100 g of cookies.